The Effect Of Brand Image, Quality Of Service And Location On Purchase Decisions At Other Heart Coffee Stores - Wargianto Wargianto; Andi Eko Wardana (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2022)
This study aims to analyze the effect of brand image, service quality and location on purchasing decisions at other coffee shops (a case study on consumers in Pangkalpinang City). The type of research used is explanatory research with a quantitative approach and also uses a causal relationship (cause and effect) between variables. The research model is hypothesis testing, which tests the theoretical relationship built by the researcher. The data used are secondary data and primary data collected from research respondents, namely other coffee shop customers in the city of Pangandaran with a total sample of 100 people. The data analysis technique used multiple linear regression analysis. The results showed that brand image, service quality and location had a positive and significant effect on purchasing decisions at the Lain Hati Coffee shop.